The Effects of a Breastfeeding Support Program for Couples Based on Self-Determination Theory on Breastfeeding Outcomes - Gürol, Serpil; Turfan, Esin Çeber (International Journal of Child Health and Nutrition, 2026)
Objective: This study aimed to investigate the effects of a Breastfeeding Support Program for Couples Based on Self-Determination Theory on Breastfeeding Outcomes. Method: The study was carried out between 01.12.2021 and 15.03.2023 with a randomized controlled educational intervention design, where couples who presented to İzmir Torbalı Family Health Center (FHC) No 1 were included in a Breastfeeding Support Program for Couples in the intervention group and Standard Breastfeeding Education in the control group by a midwife by the 32nd week of pregnancy. Results: Significant positive relationships were identified between the Breastfeeding Support Scale for Couples scores of the mothers and those of the fathers at the 15th day, 2nd month, 4th month, and 6th month in the postpartum period (p<0.01). At 6 months, among couples who participated in the Breastfeeding Support Program for Couples (intervention group), as Breastfeeding Support Scale scores increased, mothers' Breastfeeding Motivation Scale scores increased. It was determined that the breastfeeding efficacy levels of the mothers in the intervention and control groups started to increase after the 7th day in the postpartum period, and their mean Breastfeeding Self-Efficacy Scale scores were high. The mothers who participated in the Breastfeeding Support Program for Couples had a lower rate of experiencing Nipple Pain and Trauma and a higher rate of feeding their babies exclusively with breastmilk in the first six months of the postpartum period. Conclusion: In conclusion, fathers who participated in the Breastfeeding Support Program for Couples improved the breastfeeding outcomes of their partners, the program was effective in reducing nipple problems, and mothers who participated in the program had a higher rate of feeding their babies exclusively with breastmilk in the first six months of the postpartum period.